Psychological well-being among Gen Z social media users: Exploring the role of self-esteem and social media dependency as mediators and social media usage motives as moderator - Pertiwi, Era Mutiara; Suminar, Dewi Retno; Ardi, Rahkman (Universitas Muhammadiyah Surakarta, 2022)
Abstract. Social media has become an inseparable part of Gen Z’s life. However, a number of previous research documented contradictive findings regarding social media use and its effect on psychological wellbeing among adolescents. This study aimed to investigate the role of self-esteem, social media dependency, and motives of social media use in the psychological well-being of Gen Z adolescents. A total of 647 students (aged 12 to 21 years, comprising 282 males and 365 females) participated and completed several self-reported instruments, including the Rosenberg Self-Esteem Scale (RSES), the Online Social Network Dependency Scale (OSNDS), the Social Media Usage Motives Scale (SMUMS), and the Mental Health Inventory (MHI-18). Results from Structural Equation Modelling (SEM) showed that self-esteem was a positive predictor, while social media dependency was a negative predictor of psychological well-being in Gen Z adolescents. Social media dependency was also found significantly mediate the link between self-esteem and psychological well-being. In addition, motives for social media use were a significant moderator of the relationship between social media dependency and psychological well-being, in which a maintaining existing relationship motive intensified this association, while a meet new people and socializing motive weakened it. These findings implied the importance of an intervention targeting selfesteem in understanding the motive behind adolescents’ use of social media so that their consumption of social media could be appropriate and offer benefits for their psychological well-being.Keywords: gen Z; psychological well-being; self-esteem; social media dependency; social media use motive.